Social Protection and Climate Disasters: Brazil's Responses to the 2024 Rio Grande do Sul Floods - Raquel Tebaldi (United Nations University (UNU), Maastricht Economic and Social Research Institute on Innovation and Technology (UNU-MERIT), 2025)
The 2024 floods in the state of Rio Grande do Sul, Brazil, prompted the largest and fastest response to an extreme weather event in the country's history. Brazil is a compelling case for analysing shock-responsive and climate-adaptive social protection because of its high level of decentralisation and significant maturity of its social protection system. Brazil is also highly susceptible to climate risks, and as climate change intensifies, bringing more frequent and severe weather events, strengthening the resilience of social protection systems becomes increasingly vital. This case study examines the Brazilian government's emergency responses, with a particular focus on the federal and state interventions, drawing from documental analysis and key informant interviews. The analysis shows how significant levels of emergency support were mobilised by federal and state governments, and the system features that enabled a quick response, such as the use of technology for mapping affected areas and the use of existing government databases. Nonetheless, actors faced challenges in terms of coordination between different levels of governance and in terms of emergency preparedness. This study provides some reflections on the obstacles encountered by federal and state actors and points to areas for further improvement at the system level.
Keywords: I38; H53; H84; Q54; 330; adaptive social protection; shock-responsive social protection; climate change; climate crisis; Rio Grande do Sul floods